Knowledge, attitudes, and behaviors toward COVID-19 vaccination in a sample of Italian healthcare workers - Luca Regazzi; Eleonora Marziali; Alberto Lontano; Leonardo Villani; Andrea Paladini; Giovanna Elisa Calabrò; Patrizia Laurenti; Walter Ricciardi; Chiara Cadeddu (Taylor & Francis Group, 2022)
Vaccine hesitancy in healthcare workers (HCWs) has been studied for various contagious diseases, but there is still insufficient knowledge about this phenomenon for COVID-19. We developed and validated a knowledge, attitude, and practice survey of 39 questions to assess Italian HCWs' hesitancy toward vaccination in general (general hesitancy), COVID-19 vaccination (COVID-19 hesitancy), and public health injunctive measures (refusal of obligations). The survey was administered through a web platform between July and November 2021. Three multivariable logistic regressions were performed to evaluate the association between the explored dimensions of hesitancy and the potential determinants investigated. Out of 2,132 respondents with complete answers, 17.0% showed to be generally hesitancy toward vaccination, 32.3% were hesitant on COVID-19 vaccination, while 18.8% were categorized as refusing obligations. A significant protective effect against all three dimensions of hesitancy was found for increasing fear of COVID-19, advising COVID-19 vaccination to relatives and patients, having received flu vaccination in the previous year and having higher levels of education. Better self-rated knowledge about COVID-19 vaccines and reading up institutional sources were significantly protective against general and COVID-19 hesitancy, while being a physician rather than another healthcare professional was protective only against COVID-19 hesitancy. Conversely, increasing age and referring to colleagues to expand knowledge about COVID-19 were positively associated with COVID-19 hesitancy. The determinants of general hesitancy, COVID-19 hesitancy and the refusal of obligations are mostly overlapping. Given the great influence they exert on patients and communities, it is pivotal to limit HCWs vaccine hesitancy through appropriate training activities.